Electrodeposition of uniform granular carbon on an Ag electrode by CO2 reduction in triethylpentylphosphonium bis(trifluoromethanesulfonyl)imide - Yuki Kakiuchi; Yuta Suzuki; Hidekazu Kobatake; Seiya Tanaka; Takuya Goto (Electrochemistry Communications, 2025)
Carbon electrodeposition on a conductive substrate from CO2 in ionic liquids is an attractive process for a unique CO2 conversion technique. This study provides a method for the electrodeposition of uniformly arranged granular carbon particles onto an Ag substrate from CO2 by potential-step application in P2225-TFSI at room temperature. The potential-step electrolysis, where the −3.0 and −0.40 V (vs. Ag+/Ag) were applied for 1 min each, followed by −1.0 V for 3.2 s for 20 sets, was conducted to reduce CO2 to silver carbonyl ions and then to solid carbon electrochemically. The SEM image with EDS elemental analysis for the electrodeposits exhibited that granular carbon particles uniformly arranged and ca. 0.4 μm in size were covered on the Ag surface. This result indicates that carbon nucleation could be preferentially induced at the Ag/P2225-TFSI interface when applying the potential in the third step for a few seconds. Raman spectroscopy and XRD analyses revealed that the electrodeposited carbon grains comprised hexagonal carbon, graphite, and η-diamond. Moreover, we proposed a model for the formation mechanism of the carbon grains on the Ag substrate in the electrolysis based on the observed morphological changes in the electrodeposited carbon when the number of times the step electrolysis was changed. The reported data demonstrated that it is possible to electrochemically control the nucleation and growth phenomena of carbon from CO2 at room temperature, which is expected to contribute to producing functional carbon materials as a novel CO2 recycling technology.